2023
DOI: 10.1021/acs.cgd.2c01137
|View full text |Cite
|
Sign up to set email alerts
|

Designing the Mechanical Plasticity of Benzylidene Indanones Based Molecular Crystals by Crystal Engineering

Abstract: We herein report the tuning of mechanical plasticity of a series of 2-benzylidene-1-indanone derivative crystals through controlling intermolecular interactions for the first time. The roles of intermolecular interactions on plastic properties are rationalized by nanoindentation and energy framework calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Crystals may exhibit several mechanical macroscopic properties when exposed to stimuli, such as stress, 1-3 light, [4][5][6] heat, [7][8][9] and humidity. 10,11 Stress-induced mechanical properties of molecular crystals can be of different types based on the packing arrangement, such as elasticity, [12][13][14][15] plasticity, [16][17][18] twinning, 19,20 and helical twisting. 21,22 In photosalient and thermosalient crystals, molecular rearrangement triggered by light and heat can induce distinct mechanical responses.…”
Section: Introductionmentioning
confidence: 99%
“…Crystals may exhibit several mechanical macroscopic properties when exposed to stimuli, such as stress, 1-3 light, [4][5][6] heat, [7][8][9] and humidity. 10,11 Stress-induced mechanical properties of molecular crystals can be of different types based on the packing arrangement, such as elasticity, [12][13][14][15] plasticity, [16][17][18] twinning, 19,20 and helical twisting. 21,22 In photosalient and thermosalient crystals, molecular rearrangement triggered by light and heat can induce distinct mechanical responses.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Ghosh et al demonstrated the modulation of plastic behaviour by peripheral substituent changes around the centrally located aromatic ring. 12 The study also highlighted that the regulation of complementary shape synthons may lead to controllable plasticity. In our current report, we have shown that by changing the intervening linker molecule, mechanical properties can be changed drastically from plastic to elastic.…”
Section: Introductionmentioning
confidence: 98%
“…9 Designing plastic molecular crystals using complementary shape synthons was well discussed by many groups. [10][11][12] Plastic molecular crystals undergo irreversible deformation under external stress. Earlier hypothesis pointed out that bending was facilitated by the segregation of flexible layers mediated by weak intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Since Reddy and Ghosh first reported an elastic crystal, widespread attention has been focused on flexible organic crystals. It is found that abundant weak intermolecular interactions, corrugated molecular arrangements, and no-slip planes are conducive to elastic bending . On the contrary, anisotropic interactions and layered structures with slip planes are the pivotal factors for plastic crystals . Clegg et al further indicated that the subtle differences in intermolecular interactions and molecular arrangements can cause drastically different flexibilities .…”
Section: Introductionmentioning
confidence: 99%
“…15 On the contrary, anisotropic interactions and layered structures with slip planes are the pivotal factors for plastic crystals. 16 Clegg et al further indicated that the subtle differences in intermolecular interactions and molecular arrangements can cause drastically different flexibilities. 17 Therefore, designing flexible crystals is still serendipitous, especially for flexible crystals with functions.…”
Section: Introductionmentioning
confidence: 99%